How to rise the minimum standard of mathematics exam? - Dargytė, Janina; Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2008)
The article is based on the achievements of 1,928 pupils of the 10th form, who participated in the national research in 2006. They were attributed to one of the four groups (low, satisfactory, basic and higher) depending on their level of achievements. The article reveals skills and abilities in each group in seven activity areas presented in the Curriculum. The majority of these pupils are expected to take state mathematics exam, therefore, so the results of the analysis provided can be useful for teachers, as well as for authors of textbooks, syllabus and exam papers.